Accountability, Transparency, and Sustainability of Zakat Distribution for Palestine from Indonesia - Khusni Mubarok (Yayasan Mitra Peduli Indonesia, 2026)
This study aims to examine the accountability and transparency of humanitarian aid distribution from Indonesia to Palestine through the National Board for Zakat Indonesia (BAZNAS). Using bibliometric analysis and literature review, this paper explores the challenges of cross-border distribution, including geopolitical barriers, logistical constraints, and donor trust issues. Data were collected from BAZNAS annual reports (2023–2025) and Scopus-indexed publications with keywords in Indonesian, including “humanitarian aid”, “Palestine”, “international aid”, and “donor”. The findings show that although Indonesia remains active in providing critical support—from food packages to cooperation funds with UNRWA—the process still faces significant obstacles, including Israeli border restrictions, delayed access to Gaza, and an unintegrated reporting system. Interviews with key informants also confirmed the physical and administrative difficulties experienced by officers in the field. However, there are still gaps in the integrated reporting mechanism and third-party audits that need to be addressed to ensure full accountability. The implications of this study offer policy recommendations to enhance aid efficiency, strengthen digital reporting systems, and enhance diplomatic coordination, thereby facilitating faster, more targeted, and more transparent aid distribution.